The beginner's Bible : timeless children's stories. (Grand Rapids, Michigan : Zondervan, 2016)
"The easy-to-read text and bright, full-color illustrations on every page make it a perfect way to introduce young children to the stories and characters of the Bible. With new vibrant three-dimensional art and compelling text, more than 90 Bible stories come to life. Kids ages 6 and under will enjoy the fun illustrations of Noah helping the elephant onto the ark, Jonah praying inside the fish, and more, as they discover The Beginner's Bible."--Amazon.
The beginning -- Adam and Eve -- The sneaky snake -- Noah's Ark -- The tall tower -- A new home -- The visitors -- A bride for Isaac -- Isaac's blessing -- Jacob's dream -- Jacob and Esau meet again -- Joseph's colorful robe -- Pharaoh's dreams -- Joseph saves his family -- A baby in a basket -- The burning bush -- Ten plagues -- Teh Red Sea -- Food from heaven -- Ten Commandments -- Twelve spies -- Joshua and the spies -- The battle of Jericho -- Deborah leads the way -- Gideon's battle -- Samson -- Ruth and Naomi -- Hannah's prayer -- A voice in the night -- Israel's first king -- A good heart -- David and Goliath -- Best friends -- King David -- The Lord is my Shepherd -- The wise King -- God watches over Elijah -- Elijah helps a widow -- fire from heaven -- Chariot of fire -- Jars of oil -- Elisha's room -- Naaman is healed -- Boy King Josiah -- The brave queen -- Fiery furnace -- Daniel and the lions -- Jonah and the big fish -- An angel visits Mary -- Baby Jesus is born -- Shepherds visit -- Simeon and Anna meet baby Jesus -- The bright star and three visitors -- An angry king -- Jesus is lost! -- John Baptizes Jesus -- Jesus chooses His disciples -- Jesus' first miracle -- Jesus teaches on a mountain -- The Lord's Prayer -- A captain's faith -- A hole in the roof -- Jesus calms the storm -- Two miracles -- A fisherman's net -- Jesus feeds thousands -- Jesus walks on water -- Jesus heals a blind beggar -- Money in a fish -- The Good Samaritan -- Mary and Martha -- The lost sheep -- The lost son -- Ten lepers -- Jesus and the children -- A short man -- Lazarus lives again -- A gift for Jesus -- The true king -- A poor widow's gift -- Washing the disciples' feet -- The Last Supper -- Jesus is arrested and crucified -- Jesus is risen! -- Jesus returns -- A net full of fish -- Jesus goes to heaven -- The Holy Spirit comes -- The first church -- The lame men -- A changed man -- Paul's journeys -- Earthquake in prison -- Jesus is coming!
Ages 4-8.
Keywords: Bible stories, English -- Juvenile literature; Bible stories, English; Bible stories, English